2016
DOI: 10.14359/51689456
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and High-Strength Hooked Bars—Part 1: Anchorage Tests

Abstract: Keywords: anchorage; beam-column joints; bond and development; highstrength concrete; high-strength steel; hooks; reinforced concrete; reinforcement. INTRODUCTIONProvisions for calculating the development length of hooked bars in U.S. design codes, such as the ACI 318-14, "Building Code Requirements for Structural Concrete"; ACI 349-06, "Code Requirements for Nuclear Safety-Related Concrete Structures"; and the "AASHTO LRFD Bridge Design Specifications" (AASHTO 2012) are based primarily on studies performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 3 publications
3
29
0
Order By: Relevance
“…This analysis shows that the bar stress predicted by Eq. (2) becomes progressively less conservative as the concrete compressive strength and bar size increase, matching the observations by Sperry et al (2017a).…”
Section: Test Results Compared To Aci 318-14supporting
confidence: 74%
See 4 more Smart Citations
“…This analysis shows that the bar stress predicted by Eq. (2) becomes progressively less conservative as the concrete compressive strength and bar size increase, matching the observations by Sperry et al (2017a).…”
Section: Test Results Compared To Aci 318-14supporting
confidence: 74%
“…Ajaam et al (2017) measured strain along the straight portion of the hooked bars and on hoops serving as the confining reinforcement within the joint region. The results showed that hoops oriented parallel to the embedment length of hooked bars and located within eight to 10 bar diameters of the straight portion of the hooked bar within the joint region exhibited increases in strain at earlier loading stages than those located further away from the hooked bars and yielded prior to hooked bar anchorage failure, confirming the previous findings by Sperry et al (2015bSperry et al ( , 2017b.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations